2015
DOI: 10.3389/fpls.2015.00652
|View full text |Cite
|
Sign up to set email alerts
|

Whole plant acclimation responses by finger millet to low nitrogen stress

Abstract: The small grain cereal, finger millet (FM, Eleusine coracana L. Gaertn), is valued by subsistence farmers in India and East Africa as a low-input crop. It is reported by farmers to require no added nitrogen (N), or only residual N, to produce grain. Exact mechanisms underlying the acclimation responses of FM to low N are largely unknown, both above and below ground. In particular, the responses of FM roots and root hairs to N or any other nutrient have not previously been reported. Given its low N requirement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
2
19
1
Order By: Relevance
“…Yield differences across sites in the present study are likely a result of more rainfall at Nioro 2018 As demonstrated by several authors, rainfall plays a critical role in crop growth and yields under rainfed agriculture (Biazin, Sterk, Temesgen, Abdulkedir, & Stroosnijder, 2012;Rockström, Barron, & Fox, 2003). Although grain yield has been reported to be positively correlated with biomass production in millet (Goron, Bhosekar, Shearer, Watts, & Raizada, 2015;Muchow, 1989), we observed the opposite in the present study. Millet produced higher grain yield and lower dry biomass at Nioro 2018, while millet plants yielded less grain but had higher stem, leaf, panicle, and dry biomass at Bambey 2017.…”
Section: Discussionsupporting
confidence: 46%
“…Yield differences across sites in the present study are likely a result of more rainfall at Nioro 2018 As demonstrated by several authors, rainfall plays a critical role in crop growth and yields under rainfed agriculture (Biazin, Sterk, Temesgen, Abdulkedir, & Stroosnijder, 2012;Rockström, Barron, & Fox, 2003). Although grain yield has been reported to be positively correlated with biomass production in millet (Goron, Bhosekar, Shearer, Watts, & Raizada, 2015;Muchow, 1989), we observed the opposite in the present study. Millet produced higher grain yield and lower dry biomass at Nioro 2018, while millet plants yielded less grain but had higher stem, leaf, panicle, and dry biomass at Bambey 2017.…”
Section: Discussionsupporting
confidence: 46%
“…1). It could be more related to lowering shoot density in grass plants under low N (Goron et al, 2015). Across 10 cool-season grass species in a controlled environment, plants responded to low N by decreasing shoot and root growth, but to a greater extent in shoots, resulting in an increase in root:shoot ratio (Skinner and Comas, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For warm-season grasses, st. augustinegrass (Stenotaphrum secundatum) had greater N partitioning to roots than bermudagrass (Cynodon dactylon), bahiagrass (Paspalum notatum), and zoysiagrass (Zoysia japonica) based on root length, root:shoot ratio, and N content in roots, suggesting that st. augustinegrass has a potential for improved N retention in roots (Poudel et al, 2013). In finger millet (Eleusine coracana), declines in shoot and root growth under low N were associated with decreased shoot tiller number, crown root number, total crown root length, and total lateral root length, but with no consistent changes in root hair traits (Goron et al, 2015). The results demonstrate that lower reductions in root growth and related morphological changes are important traits for adaptation of plants to a low-N environment.…”
mentioning
confidence: 79%
“…), a crop important in agroecosystems of the semi-arid tropics [61][62][63]. GlnLux glutamine content in finger millet leaves sampled 39 days after germination displayed tight correlation with grain yield across a range of N application rates (Supplementary Materials Figure S3C-E), conducted as part of a larger study in which N limitation effects on plant morphology were examined [64].…”
Section: Measurements Of Glnlux Glutamine At Different Growth Stages mentioning
confidence: 99%